(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the relationship between the social determinants of health with the occurrence of overweight and childhood obesity in schools in the town of Santo Amaro, in the Bahian Recôncavo. It’s an epidemiological, descriptive and quantitative cross-sectional study involving 82 schoolchildren born in 2012, enrolled in public and private schools. Sociodemographic data and eating habits were obtained through interviews with the mothers of schoolchildren at home. Birth weight and gestacional age were obtained through consultation with the child’s health card. Anthropometric data were collected from the schoolchildren and the BMI was further calculated classified according to the Z score curves recommend by the World Health Organization. A high prevalence of overweight/childhood obesity was identified (40,24%). The male sex (24.39%) compared to the female sex (15.85%), obtained a higher percentage (p<0.2255). Regarding the sociodemographic area, a high prevalence was observed in town (31,57%), with 32% living in rural areas and 68% in urban areas. Regarding inadequate eating habits, 46.72% of schoolchildren who started to consume food with a high carbohydrate rate at an early age had a higher prevalence (p<0.02479). A strong associations was verified in families with wage income below a minimum wage (p<0.0001). The analysis of the Social Determinants of Health showed to be fundamental to understand the epidemiological situation, being evidenced high rate of overweight/childhood obesity.